Ameliorative Effect of Multi Herbal Formulation on Lipid Peroxidation and Redox Dysfunction in Ethanol Induced Hepatic Imbalance - Darbar, Soumendra; Saha, Srimoyee; Pramanik, Kaushikisankar; Chattopadhyay, Atiskumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: Traditional medicine is a potent antioxidant. In the present study, we developed a multi herbal formulation and examined its anti-oxidative activities and possible protective effect of it on serum and liver lipid peroxidation and glutathione in ethanol-induced hepatic dysfunction. Materials and Methods: In this experimental study 40 Swiss albino mice were divided into 4 groups randomly; group I as control, group II as sham treated with multi herbal formulation (MHF) (300mg/kg orally, daily), group III as liver damage control and group IV as ethanol treated with multi herbal formulation (MHF) (300mg/kg orally, daily) after induce liver damage, respectively. Liver damage was induced in the 3rd and 4th groups by ethanol administration (50% v/v). Results: After sixty days, animals were anaesthetized, liver was then removed immediately and used fresh or kept frozen until analysis. Blood samples were also collected before killing of the mice to measure the lipid peroxidation and antioxidant enzymes level. Serum and Liver lipid peroxidation level (MDA level) were significantly increased in ethanol treated group compared with untreated group. However, content of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and glutathione peroxidase (GPx) in serum and liver tissue were significantly decrease in ethanol treated group compared with untreated group. Alteration of serum and liver lipid peroxidation and antioxidant enzymes content were significantly inhibited by the administration of developed multi herbal formulation (MHF) (300mg/kg orally, daily). Conclusion: In conclusion the study showed that developed multi herbal formulation (MHF) might be a potent antioxidant and exert beneficial effects on the lipid peroxidation level and maintained the antioxidant levels in ethanol-induced liver dysfunction.
Keywords: Alcohol; Liver disease; Lipid Peroxidation; Mice; Herbal Formulation; Antioxidant enzymes